Decolonizing Curricula in Bangladesh: Comparative Analysis of Indigenous Knowledge Integration Across Global South and North - Yasin Arafat; Lutfur Nahar; A. B. M Feroz Shahriar Shahriar; Kanika Chakraborty; Saifuddin Ahmad Rakib; Md. Iftekhar Arif (Goodwood Publishing, 2026)
Purpose: This study investigates the decolonization of the curriculum in Bangladesh by integrating Indigenous Knowledge (IK) to foil abiding colonial legacies. Research Methodology: This study investigates local Eurocentric biases against international models, specifically Ubuntu Pedagogy (Global South) and Canada’s Truth and Reconciliation Commission (Global North), using qualitative document analysis and a comparative framework. Results: The findings reveal that Bangladesh’s curriculum remains heavily influenced by colonial structures, marginalizing Indigenous worldviews. Although the National Education Policy 2010 acknowledges the Indigenous spirit, its implementation is hindered by resource scarcity, a lack of native-language materials, and political elite dominance. Global comparisons suggest that structural shifts are vital for achieving educational and social justice. Conclusions: The study concludes that meaningful decolonization is required to dismantle Eurocentric structures and create a contextual curriculum that includes Indigenous histories and traditions. Limitations: Relying on document analysis and limited local literature may overlook the field-level complexities and nuances of practical implementation. Contributions: This study advances the discourse on epistemic decolonization by providing a cross-regional comparative perspective to inform curriculum reform in Bangladesh.